A review study on the potential of microalgae biomass producing biopolymer material - Adil, M. Osman; Nour, Abdurahman Hamid; Noormazlinah, Ahmad (Penerbit Universiti Malaysia Pahang, 2023)
This review focuses on the potential of microalgae biomass in producing biopolymer materials. Microalgae have gained attention as a sustainable and renewable source of energy and other useful products such as biofuels, pharmaceuticals, and cosmetics. One promising application of microalgae is as a source of biopolymers, which can be used as a sustainable alternative to traditional petroleum-based plastics. The review is conducted through a comprehensive search of electronic databases, screening of relevant articles, and synthesis of information obtained from the selected studies. The review also critically evaluates the strengths and limitations of the existing research on the potential of microalgae biomass in producing biopolymer materials. The outcomes in this review highlights key findings related to the potential applications of microalgae biomass in producing biopolymers and identifies areas for future research. The conclusions and recommendations of this review are important for guiding the development of sustainable and environmentally friendly biopolymer materials.